2002
DOI: 10.1046/j.1524-4725.2002.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation System to Enhance Patient Selection for Alopecia-Reducing Surgery

Abstract: An evaluation system is presented that helps determine who is a good candidate for alopecia reduction and who is a poor candidate. This selection technique has helped the author achieve more consistently good results by eliminating poor and borderline candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This sentiment has been echoed in the experience of other institutions. 8 The reason for this observation is likely multifold. Younger patients tend to have unrealistic expectation of the density they can expect after surgery.…”
Section: Patient Selectionmentioning
confidence: 99%
“…This sentiment has been echoed in the experience of other institutions. 8 The reason for this observation is likely multifold. Younger patients tend to have unrealistic expectation of the density they can expect after surgery.…”
Section: Patient Selectionmentioning
confidence: 99%
“…He concluded that the evaluation system should help the hair restoration surgeon determine who is a good candidate for AR and who is a poor candidate. [ 32 ] Ideal candidates are males with Norwood Grade 4, 5 and 6, who are above the age of 40 with stable hair loss. These patients should have little or no hair in the scalp which is to be excised but have dense hair on the sides and back of the head (good arietal humps) with good scalp laxity.…”
Section: Patient Selection For Armentioning
confidence: 99%